Cell Line Authentication (CLA) using Short Tandem Repeat (STR) Method on Breast Cancer cell line MCF-7 - Pendrianto; Muhammad Samsul Mustofa; Silviatun Nihayah (Nusantara Science and Technology Proceedings)
Research on human diseases, especially in cancer begins with in vitro studies using cell lines. However, cell lines grown in vitro can occur cross-contamination or even miss-identification. This requires a cell line authentication (CLA) procedure using a molecular approach. In this process, analysis of allele variance from several loci is needed to ensure that this variant matches the expected allele. The STR method can be used to authenticate cell lines, because it can compare allele profiles with a sample of known standard cell lines, and also able to provide simple, inexpensive, and very specific genetic "fingerprints" on cell lines. It is necessary to authenticate cell lines in collections of cell lines in the Central Laboratory for Stem Cell Studies at the YARSI University Research Institute, so that in vitro and in vivo studies on anticancer, antioxidants, aging, and longevity involving cell lines will produce valid outcomes in future research. The research method was laboratory experimental. breast cancer cell lines MCF-7, grown on growth media containing serum and antimicrobial-antimycotic. Genomic DNA was isolated by Maxwell® RSC Whole Blood DNA Kit. PCR process using GlobalFiler™ PCR amplification Kit (Applied Biosystem) and fragment analysis was analyzed with Genetic Analyzer 3500. The preliminary results of fragment analysis on two MCF-7 lines originating from two different places indicated that these cell lines were inauthentic. Possibly due to cross contamination during activity in the laboratory. This makes the two cell lines unusable as materials in in vitro studies. There are limitations to this study because it only analyzed 1 batch of subcultures for each cell line. Further research is needed in the entire batch of culture collection in the Central Laboratory for Stem Cell Studies at the YARSI University Research Institute.